CT semi-quantitative score used as risk factor for hyponatremia in patients with COVID-19: a cross-sectional study - Wu, Baofeng; Li, Ru; Hao, Jinxuan; Qi, Yijie; Liu, Botao; Wei, Hongxia; Li, Zhe; Zhang, Yi; Liu, Yunfeng (Frontiers in Endocrinology, 2024)
PURPOSE Chest computed tomography (CT) is used to determine the severity of COVID-19 pneumonia, and pneumonia is associated with hyponatremia. This study aims to explore the predictive value of the semi-quantitative CT visual score for hyponatremia in patients with COVID-19 to provide a reference for clinical practice. METHODS In this cross-sectional study, 343 patients with RT-PCR confirmed COVID-19, all patients underwent CT, and the severity of lung lesions was scored by radiologists using the semi-quantitative CT visual score. The risk factors of hyponatremia in COVID-19 patients were analyzed and combined with laboratory tests. The thyroid function changes caused by SARS-CoV-2 infection and their interaction with hyponatremia were also analyzed. RESULTS In patients with SARS-CoV-2 infection, the total severity score(TSS) of hyponatremia was higher [M(range), 3.5(2.5-5.5)vs3.0(2.0-4.5) scores, P=0.001], implying that patients with hyponatremia had more severe lung lesions. The risk factors of hyponatremia in the multivariate regression model included age, vomiting, neutrophils, platelet, and total severity score. SARS-CoV-2 infection impacted thyroid function, and patients with hyponatremia showed a lower free triiodothyronine (3.1±0.9vs3.7±0.9, P=0.001) and thyroid stimulating hormone level [1.4(0.8-2.4)vs2.2(1.2-3.4), P=0.038]. CONCLUSION Semi-quantitative CT score can be used as a risk factor for hyponatremia in patients with COVID-19. There is a weak positive correlation between serum sodium and free triiodothyronine in patients with SARS-CoV-2 infection.